Psychological profile and impact of addiction/s amongst women attending a de-addiction center in Pune city of India - Barhate, Amruta; Pore, Prasad; Gothankar, Jayashree; Bhatia, Prakash (International Journal Of Community Medicine And Public Health, 2020)
Background: Gender differences in the medical consequences of substance use have been highlighted, with the females reporting higher physical and psychological impairment with an accelerated progression of alcoholism labeled as ‘telescoping’. The pattern and degree of psychiatric comorbidity related to substance use is different in women as compared to men. Lack of resources, lack of awareness and negative attitudes to women’s substance use contributes to the scarcity of gender-related epidemiological data and other research on women’s substance use problems. Aim was to determine the level of depression, anxiety, stress and impact of addiction/s amongst women attending a de-addiction center. Methods: The study was conducted in a randomly selected de-addiction centre in Pune city. All the women attending the de-addiction center in a year from IPD were interviewed after explaining the purpose of the study and informed consent and information was obtained from the women in a pre-designed, pretested questionnaire. The proforma consisted of questions related to their addiction, DASS scale as well as drug use questionnaire score scale. Results: In the present study, out of 45 women, 31 (68.9%) had depression, 30 (66.7%) had anxiety and 28 (62.2%) had stress. Majority 26 (57.8%) of women had moderate level of problems related to substance abuse. Majority of women had impact of addiction on marital domain of life (91.1%) followed by family (71.11%) domain, health (64.44%) and social (46.67%) domain of life. Conclusions: The study brings out psychological co-morbidities present along with addiction/s and highlights impact of addiction/s on various domains of life.